ANALISIS PENGEMBANGAN GEROBAK TARIK MOTOR BERBASIS DESAIN MODULAR UNTUK MENINGKATKAN MOBILITAS DAN KONSTRUKSI YANG AMAN DALAM BERNIAGA - Bilnadzary Rahmatullah; Abdul Rohman; Eli Novita Sari; I Gusti Ngurah Bagus Catrawedarma; IGNA Satria Prasetya D W (ELEMEN : JURNAL TEKNIK MESIN, 2026)
The development of mobility in the commercial sector drives innovation in transport tools such as motorized tow carts. This study analyzes three support frame design variations using Aluminum 6063 and Finite Element Analysis (FEA). A static load of 3,924 N was applied evenly at three points along the -Y axis. Simulation results showed that Variation 1 generated a maximum Von Mises stress of 43.409 MPa, deformation of 0.62483 mm, and safety factor of 4.9529. Variation 2 yielded stress of 35.493 MPa, deformation of 0.66134 mm, and safety factor of 6.0575. Variation 3 yielded 35.487 MPa, 0.66071 mm, and the highest safety factor of 6.0586. All values remain below the material’s yield strength of 215 MPa and above the minimum required safety factor of 1.25. Variation 3 is deemed optimal.